In Situ Observation of the Phase Transition Behavior of Shocked Baddeleyite. Issue 17 (31st August 2020) - Takagi, Sota; Kyono, Atsushi; Nozawa, Shunsuke; Kawai, Nobuaki; Inukai, Koji; Fukaya, Ryo; Funamori, Nobumasa; Adachi, Shin‐ichi; Ichiyanagi, Kouhei
Abstract: Baddeleyite (ZrO2 ) is used to infer shock pressures and understand the impact history of planetary bodies. Although the high‐pressure phase transition behavior of baddeleyite has been intensively investigated under hydrostatic conditions, there is little information on the dynamic response of phase transitions under shock‐loading conditions. We performed in situ X‐ray diffraction measurements on shock‐loaded baddeleyite using a synchrotron X‐ray pulse at beamline NW14A of the Photon Factory Advanced Ring, High Energy Accelerator Research Organization (KEK), Japan. A phase transition from monoclinic to orthorhombic‐I ZrO2 occurs at 3.3 GPa during shock compression and immediately returns to the monoclinic phase during subsequent release. Orthorhombic‐II ZrO2 is not observed up to 15 GPa. This study refines the phase transition behavior of baddeleyite under shock conditions up to 15 GPa, and the phase transition boundary is determined from direct observations. These findings improve the understanding of the shock history of planetary bodies. Plain Language Summary: Understanding the amount of pressure generated by an impact event between astronomical objects is essential for studying solar system evolution. Baddeleyite (ZrO2 ) is a widespread mineral found in the Earth, Moon, Mars, and meteorites and can be applied as a shock‐pressure barometer and geochronometer. Impact events induce instantaneous high‐pressure conditions (on the order of giga [10 12 ] pascals [GPa]), which is referred to as shock compression. The crystal structure of baddeleyite is known to change under such high‐pressure conditions; however, this transformation has not been directly observed under shock compression due to experimental difficulties. In this study, we directly observed the baddeleyite phase transformation in shock experiments performed at a synchrotron facility (Photon Factory Advanced Ring, High Energy Accelerator Research Organization (KEK), Japan). A high‐power laser was used to generate the shock wave, and the crystal structural response during the shock compression was detected using a synchrotron X‐ray pulse. The time‐resolved X‐ray diffraction measurements show that baddeleyite's crystal structure transforms to the high‐pressure phase during shock compression at 3.3 GPa but immediately returns back to the low‐pressure phase upon decompression. Our results can be used to estimate the size of past planetary impact events and better understand mineral behavior under shock conditions. Key Points: A phase transition in baddeleyite is directly observed under shock wave loading by in situ time‐resolved X‐ray diffraction A phase transition occurs from baddeleyite to orthorhombic‐I ZrO2 at 3.3 GPa, but immediately returns to baddeleyite upon decompression The baddeleyite‐orthorhombic‐I ZrO2 phase transition during shock compression is similar to that during static compression